Impact of Perceived Barriers on Patient Engagement and Attitudes towards Transition and Transfer - Megan Drovetta; Emily Cramer; Alaina Linafelter; Jordan Sevart; Michele Maddux (MDPI AG, 2022)
Objective: This study is a preliminary evaluation of how perceived barriers towards transition might impact patient attitudes towards their own readiness and ability to transition, self-efficacy towards their IBD, and the allocation of treatment responsibility. Methods: A sample of 81 young adults with IBD were seen for standard care in a Young Adult Clinic (YAC). Patients completed questionnaires on perceived transition barriers; perceived confidence, importance, motivation, and readiness towards transition and transfer; IBD self-efficacy; and allocation of treatment responsibility. Path model analyses were conducted. Results: Not knowing how and who to transfer to and not understanding insurance details were the most commonly endorsed perceived barriers to transition. A significant relationship was found between the attitude toward transition and allocation of treatment responsibility, but no meaningful indirect effects were found from perceived barriers to the allocation of treatment responsibility, using attitudes toward transition as an intervening variable. The relationship between perceived barriers and allocation of treatment responsibility was at least partially explained by examining the intervening effects of attitudes toward transfer and self-efficacy. Conclusions: The study findings carry important implications for targets of clinical intervention to assist young adults with IBD in engaging in their health care and ultimately transferring into adult care.